Diversity, Equity, and Inclusion in the Workplace: A Bibliometric Perspective on the Role of HR in Building Inclusive Cultures - Loso Judijanto; Asmirin Noor; Muhamad Ammar Muhtadi (Westscience Press, 2025)
Diversity, Equity, and Inclusion (DEI) have become essential components of modern workplace strategies, with Human Resource Management (HRM) playing a critical role in fostering inclusive cultures. This study employs a bibliometric analysis of literature from the Scopus database to examine the evolving role of HR in DEI initiatives. Using VOSviewer, the research maps key themes, influential authors, and emerging trends in DEI-related HR studies. Findings indicate that organizational culture, job satisfaction, and employee engagement are central to DEI discussions, emphasizing the need for HR to embed inclusivity into workplace policies and practices. The study also reveals increasing research on psychological well-being, mental health, and intersectionality, highlighting a shift toward a more holistic and people-centered approach to DEI. Despite the progress, challenges remain in effectively implementing DEI strategies, particularly in measuring inclusion, addressing unconscious bias, and adapting global DEI frameworks. The study concludes that HR must adopt data-driven, context-aware, and intersectional approaches to foster sustainable and impactful DEI initiatives. Future research should explore the integration of AI and big data in DEI measurement, as well as the role of leadership in driving long-term inclusivity.